Investigation of non-alcoholic steatohepatitis in labidochromis caeruleus and xiphophorus hellerii - Mustafa Ünal Boyraz; Muhammet Yaşar Dörtbudak; Muhammet Bahıttin Dörtbudak (Eurasian Journal of Veterinary Sciences)
Aim: "Labidochromis caeruleus" and "Xiphophorus hellerii" are commercially important aquarium ornamental fish. The aim of this study, upon the discovery that these species died by showing various clinical signs in optimum conditions and standard feding conditions, was to investigate the causes of death and to determine the problems that may be encountered in the field. Materials and Methods: In our study, five of Labidochromis caeruleus and Xiphophorus hellerii, which were grown as seven species of ornamental fishes and died with similar clinical symptoms were used. Because of the changes observed in the liver, macroscopically, liver dissection, and HxE staining were carried out respectively and examined by light microscopy. Results: Serosangioz exudate in the abdomen, anemi, livers yellow-brown, lipidosis with inflammation, excessive growth, crispandeasily degradable consistency, bluntends and petechial hemorrhage foci were observed. Microscopically seen that the hepatocyte cytoplasms were filled by large oil droplets with macro and micro vesicular. Fatty changes in liver cells are widely distributed from central veins toward hepatocytes in the middle of the lobule and periportal areas. Conclusion: The histopathological changes in the liver were investigated and under optimum conditions and standard feding conditions, and the sensitivities of these commercially important aquarium ornamental fishes were determined against market baits. It has been concluded that the sespecies can be a model organism for studies on fatty liver thanks to widespread/clear visualization of fatty liver and observation of a case of steatohepatitis, which is an important health problem and has not been previously reported for Labidochromis caeruleus and Xiphophorus hellerii species.